Aging resistance of polyurethane/graphene oxide composite modified asphalt: performance evaluation and molecular dynamics simulation. Issue 3 (11th February 2023) - Wang, Qian; Yu, Ruien; Cai, Lina; Chen, Xiaowen; Zhu, Xijing; Xiao, Yue; Zhang, Xiaoyan; Zhou, Xing; Fang, Changqing
ABSTRACT: To evaluate the effect of polymers and nanomaterials on asphalt after thermo-oxidative aging, the aging resistance of thermoplastic polyurethane modified asphalt (PU-MA), polyurethane/graphene oxide composite modified asphalt (PU/GO-MA) were discussed through experiments and molecular dynamics (MD) simulations. The molecular composition and self-healing ability of aged asphalt were investigated. Base asphalt and virgin asphalt were used as control. The aging experiments of base asphalt, PU-MA and asphalt modified with PU and different content of GO composites were carried out by rolling thin-film oven test. The differential scanning calorimeter, thermal gravimetric analyzer, viscous flow deformation, bending beam rheometer and Fourier transform infrared spectrometer tests were carried out. The molecules and cracks models of asphalt were simulated by MD. The parameters such as mean square displacement, fractional free volume, dipole moment and viscosity were calculated. The results show that PU/GO can affect the transformation among components, increase the melting temperature of asphalt, improve the migration ability of asphalt molecules, enhance the self-healing diffusion movement of asphalt molecules and reduce the energy and viscosity of aged asphalt. In brief, nano and chemical synergistic modification has effects on the properties of asphalt after aging.